Electron transfer photochromism of solid-state supramolecules constructed by cucurbit[n]uril (n = 5–8) and 1-(4-carboxybenzyl)-4-[2-(4-pyridyl)-vinyl]-pyridinium chloride. (18th November 2021) - Wang, Qin; Liu, Mei-Chen; Sun, Wen-Qi; Lin, Rui-Lian; Liu, Jing-Xin
Abstract : Solid-state supramolecular complexes of a bispyridinium ethylene derivative with cucurbit[ n = 5–8]uril exhibit fast responsive photochromic properties, which are caused by the electron transfer from the host to the guest. Abstract : Incorporation of the potential photochromic compound 1-(4-carboxybenzyl)-4-[2-(4-pyridyl)-vinyl]-pyridinium chloride (guest 1 + ·Cl − ) into the macrocyclic hosts cucurbit[ n ]uril ( n = 5–8, Q[ n ]) generated a new kind of photochromic material. NMR and UV spectra confirm that the guest 1 + displays different binding models with the Q[ n ]s, which depends on the amount of the guest 1 + and the cavity size of the hosts. Photochromic properties of the complexes of 1 + ·Cl − with Q[ n ]s were investigated by solid-state UV-vis diffuse-reflectance and electron-spin resonance (ESR) spectroscopy, which indicate that the photochromic behaviors are caused by the generation of free radical 1˙ via the electron transfer from the hosts to the guest. Ab initio calculations were also carried out to discuss the effects of the Q[ n ] on photochromic behaviors.